Inflammation status in HIV-positive individuals correlates with changes in bone tissue quality after initiation of ART. (14th February 2019) - Lerma-Chippirraz, E; Pineda-Moncusí, Marta; González-Mena, A; Soldado-Folgado, Jade; Knobel, H; Trenchs-Rodríguez, M; Díez-Pérez, A; Brown, Todd T; García-Giralt, N; Güerri-Fernández, R
Abstract: Background: The mechanisms behind ART-induced bone changes in HIV-infected patients are poorly known. We aimed to analyse changes in inflammatory and bone markers in HIV after tenofovir disoproxil fumarate initiation, and the associations with changes in the bone strength parameters. Methods: HIV-positive participants starting tenofovir disoproxil fumarate-based ART underwent dual-energy X-ray absorptiometry (QDR 4500 SL ®, Hologic, Waltham, MA, USA) for bone mineral density (BMD), a microindentation test (OsteoProbe ®, Active Life Scientific, Santa Barbara, CA, USA) for bone quality [bone material strength index (BMSi)] and phlebotomy at baseline and 48 weeks after ART. A panel of inflammatory biomarkers and bone turnover markers were measured by ELISA. HIV-negative controls underwent identical procedures once. Values are expressed as medians and IQRs, and non-parametric tests were used to perform the analysis. Results: Twenty HIV-infected individuals and 20 HIV-negative control individuals were matched in terms of age and gender. HIV individuals showed higher levels of inflammatory markers. We found no differences in bone turnover markers. HIV-positive individuals presented lower BMSi values at baseline compared with controls [86 (83–90) versus 89 (88–93), respectively; P = 0.034]. We found no difference in BMD (at either of the sites evaluated). BMSi tended to increase with treatment. IL-1β at baseline was positively correlated with changes in BMSi after ART (rho = 0.564, P = 0.014). Baseline levels of sclerostin tended to be negatively correlated with changes in BMSi (rho = −0.402, P = 0.097). We found a negative correlation between time since HIV diagnosis and changes in BMSi (rho = −0.466, P = 0.04). Conclusions: We observed a correlation between changes in bone quality and the inflammatory environment in HIV-positive individuals. Moreover, among the underlying mechanisms we highlight the Wnt pathway as having a potentially significant role in ART bone quality recovery.